Population uptake of HIV testing, treatment, viral suppression, and male circumcision following a community-based intervention in Botswana (Ya Tsie/BCPP): a cluster-randomised trial. Issue 6 (June 2020) - Wirth, Kathleen E; Gaolathe, Tendani; Pretorius Holme, Molly; Mmalane, Mompati; Kadima, Etienne; Chakalisa, Unoda; Manyake, Kutlo; Matildah Mbikiwa, Atang; Simon, Selebaleng V; Letlhogile, Rona; Mukokomani, Kutlwano; van Widenfelt, Erik; et al.
Summary: Background: In settings with high HIV prevalence and treatment coverage, such as Botswana, it is unknown whether uptake of HIV prevention and treatment interventions can be increased further. We sought to determine whether a community-based intervention to identify and rapidly treat people living with HIV, and support male circumcision could increase population levels of HIV diagnosis, treatment, viral suppression, and male circumcision in Botswana. Methods: The Ya Tsie Botswana Combination Prevention Project study was a pair-matched cluster-randomised trial done in 30 communities across Botswana done from Oct 30, 2013, to June 30, 2018. 15 communities were randomly assigned to receive HIV prevention and treatment interventions, including enhanced HIV testing, earlier antiretroviral therapy (ART), and strengthened male circumcision services, and 15 received standard of care. The first primary endpoint of HIV incidence has already been reported. In this Article, we report findings for the second primary endpoint of population uptake of HIV prevention services, as measured by proportion of people known to be HIV-positive or tested HIV-negative in the preceding 12 months; proportion of people living with HIV diagnosed and on ART; proportion of people living with HIV on ART with viral suppression; and proportion of HIV-negative men circumcised. A longitudinal cohort of residents aged 16–64 years from a random, approximately 20% sample of households across the 15 communities was enrolled to assess baseline uptake of study outcomes; we also administered an end-of-study survey to all residents not previously enrolled in the longitudinal cohort to provide study end coverage estimates. Differences in intervention uptake over time by randomisation group were tested via paired Student's t test. The study has been completed and is registered with ClinicalTrials.gov (NCT01965470 ). Findings: In the six communities participating in the end-of-study survey, 2625 residents (n=1304 from standard-of-care communities, n=1321 from intervention communities) were enrolled into the 20% longitudinal cohort at baseline from Oct 30, 2013, to Nov 24, 2015. In the same communities, 10 791 (86%) of 12 489 eligible enumerated residents not previously enrolled in the longitudinal cohort participated in the end-of-study survey from March 30, 2017, to Feb 25, 2018 (5896 in intervention and 4895 in standard-of-care communities). At study end, in intervention communities, 1228 people living with HIV (91% of 1353) were on ART; 1166 people living with HIV (88% of 1321 with available viral load) were virally suppressed, and 673 HIV-negative men (40% of 1673) were circumcised in intervention communities. After accounting for baseline differences, at study end the proportion of people living with HIV who were diagnosed was significantly higher in intervention communities (absolute increase of 9% to 93%) compared with standard-of-care communities (absolute increase of 2% to 88%; prevalence ratio [PR] 1·08 [95% CI 1·02–1·14], p=0·032). Population levels of ART, viral suppression, and male circumcision increased from baseline in both groups, with greater increases in intervention communities (ART PR 1·12 [95% CI 1·07–1·17], p=0·018; viral suppression 1·13 [1·09–1·17], p=0·017; male circumcision 1·26 [1·17–1·35], p=0·029). Interpretation: It is possible to achieve very high population levels of HIV testing and treatment in a high-prevalence setting. Maintaining these coverage levels over the next decade could substantially reduce HIV transmission and potentially eliminate the epidemic in these areas. Funding: US President's Emergency Plan for AIDS Relief through the Centers for Disease Control and Prevention.